Menggali Perangkat Keilmuan Islam sebagai Basis Pengembangan Nilai-Nilai Universal Penalaran Moral Post-Conventional - Yaqin, Ainul; Syarif, M.; Rohmad, Muhammad Ali (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
Post-conventional is the highest level of moral reasoning based on cognitive developmental moral theory. As the highest level, post-conventional is the level of moral reasoning that everyone (including Muslims) needs to have because a person's moral reasoning is correlated with his moral actions. Moral reasoning affects how a person believes that behavior should be done. A person has reached the post-conventional level if his moral reasoning refers to universal values ​​such as justice, equality, humanity, and so on. In Muslim society, the acceptance of universal values ​​that form the basis for this post-conventional level of moral reasoning is still debated. This article examines the thoughts of Muslim scholars who present explanations of Islamic scientific tools (maqashid al-shariah, maslahah, and naskh-mansukh), which give place to universal principles. The results of this study conclude that a Muslim has the opportunity to reach a post-conventional moral level because his religious teachings provide a foundation based on universal values ​​as well as a post-conventional moral level foundation. Based on the results of this study, Islamic education can use the reference of cognitive-developmental moral theory to be used in the formation of students' moral reasoning to the highest level; post-conventional.